Exploring the perception of lifestyle housing development in Malaysia - Abdul Ghani, S.; Lee, Y.F. (2015)
The concept of lifestyle has been the subject of interest in housing research. The emergence-of lifestyle living environment can be seen in many real estate developments particularly in urban neighbourhood. Housing image in Malaysia has evolved significantly in the last decade due to changes in the purchasers' preference, socio-economic factors, and advancement of technology as well as increase in the level of education and income among the urbanites. Although many studies have been carried out in reviewing the design and architectural aspects in the contemporary houses in Malaysia, little is known about the house buyers' preferences and demand for lifestyle housing, and how property developers customized their products in meeting the purchasers' changing needs. The purpose of this study is to identity the unique: property features that the house buyers looking for as a retlection of the change in their lifestyle and standards of living. A total of 117 responses were collected from potential house buyers in Kuala Lumpur, through questionnalre survey. The respondents were represented by those who are actively looking to buy a house and currently evaluating their housing options. The relationships between the lifestyle and their housing preferences were tested and the model of intluences on housing choice was supported. The results show that house buyers motives in housing choices are driven by a complex system of factors at the neighbourhood level and borne out across the narrative papers. The findings from this study can be applied to the design and management of lifestyle housing development and to marketing strategies that are pertinent to lifestyle concepts. It is recommended however that further research studies test the lifestyle housing with different groups in diverse markets.